2000
DOI: 10.1091/mbc.11.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Multilamellar Bodies via Autophagy

Abstract: Transfection of Mv1Lu mink lung type II alveolar cells with ␤1-6-N-acetylglucosaminyl transferase V is associated with the expression of large lysosomal vacuoles, which are immunofluorescently labeled for the lysosomal glycoprotein lysosomal-associated membrane protein-2 and the ␤1-6-branched N-glycan-specific lectin phaseolis vulgaris leucoagglutinin. By electron microscopy, the vacuoles present the morphology of multilamellar bodies (MLBs). Treatment of the cells with the lysosomal protease inhibitor leupept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
145
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 54 publications
17
145
1
2
Order By: Relevance
“…Because multilamellar bodies are produced in the lysosome from tightly packed precursor bodies through proteolytic digestion, the integrity of lysosomes may be critical for their biogenesis. Indeed, increased glycosylation of lysosomal membrane proteins, such as the lysosome-associated membrane proteins (LAMPs) (29), through acquisition of ␤1,6GlcNAc branching and polylactosamine extension, results in elevated production of multilamellar bodies (30). We observed that levels of polylactosamine-extended LAMP proteins, particularly LAMP2, were reduced in tissues from MX͞MII double-nulls (T.O.A.…”
Section: Discussionmentioning
confidence: 98%
“…Because multilamellar bodies are produced in the lysosome from tightly packed precursor bodies through proteolytic digestion, the integrity of lysosomes may be critical for their biogenesis. Indeed, increased glycosylation of lysosomal membrane proteins, such as the lysosome-associated membrane proteins (LAMPs) (29), through acquisition of ␤1,6GlcNAc branching and polylactosamine extension, results in elevated production of multilamellar bodies (30). We observed that levels of polylactosamine-extended LAMP proteins, particularly LAMP2, were reduced in tissues from MX͞MII double-nulls (T.O.A.…”
Section: Discussionmentioning
confidence: 98%
“…7, E-G) revealed an elevated level of multilamellar/multivesicular bodies as compared with WT sections. Such structures are known autophagic features (25).…”
Section: The Lysosomal/autophagic Pathway Is Locally Activated In Thementioning
confidence: 99%
“…Beclin-1/ATG6 is part of a lipid kinase complex that has been shown to play a central role in coordinating the cytoprotective function of autophagy and in opposing apoptosis (24). In addition, the activity of the lysosomal/endosomal vesicular pathway appeared to be increased in the caput epididymal epithelium of the Ido1 Ϫ/Ϫ animals, as evidenced by ultrastructural features characteristic of autophagic processes, such as the intracellular accumulation of multilamellar bodies (25). Together, these data support the idea that autophagy is up-regulated in Ido1 Ϫ/Ϫ caput epididymis to compensate for a decline in intracellular proteasome-dependent protein catabolism.…”
Section: Iaamentioning
confidence: 99%
“…Harari et al demonstrated that GnT-V transfection into mink lung cells induced production of LPHA-and CD63/LAMP-3-positive multilamellar vesicles whose formation was dependent on autophagy. 33 This suggested that GnT-V expression might have induced autophagy. Thus in principle, by adding β1,6-branched oligosaccharides to melanogenic proteins and by stimulating autophagy, GnT-V could have elicited both increased melanogenesis and the packaging of melanosomes into autophagosomes.…”
Section: β16-branched Oligosaccharides Regulate Motility and Melanogmentioning
confidence: 99%